The Effect of Return on Equity (ROE) and Earning per Share (EPS) on Stock Prices In Indonesia Stock Exchange 2015-2018 - Herlina Lusiana (Yayasan Ilomata, 2020)
This study aims to analyze the source of a company's profitability by choosing two main factors namely, Return on Equity (ROE) and Earning per Share (EPS) as the strength and resilience of companies engaged in food and beverage listed on the Indonesia Stock Exchange. This study uses time series data from 2015 to 2018. The dependent variable is the stock price. Meanwhile the independent variables are Return on Equity (ROE) and Earning per Share (EPS). The determination of the sample uses positive sampling, the sampling technique uses two special criteria from researchers. The first criterion, only food and beverage companies that publish financial statements in full during the period 2015 to 2018, and the second criterion, food and beverage companies that have financial statement data in accordance with the studied variables, namely Return on Equity (ROE) and Earning per Share (EPS). Samples that meet the criteria are 11 registered food and beverage companies on the Indonesia Stock Exchange for the period 2015 to 2018. Data analysis techniques using multiple linear regression with the help of the SPSS program.The findings show that Return on Equity (ROE) has a positive and significant impact on stock prices, while Earning per Share (EPS) has an impact negative and significant to stock prices. This finding confirms that strength the profitability of a company through Return on Equity (ROE) affects the stock prices of food and beverage companies in Indonesia. Therefore, it is important to maintain the company's profitability through Return on Equity (ROE) from the investor's perspective, not from the company's view. Meanwhile, interesting findings from a company's profitability through Earning per Share (EPS) do not affect the stock prices of food and beverage companies in Indonesia. Because earnings per share or earning per share (EPS) is obtained from the perspective of the company's financial statements where there are differences in the size and size of the company's expenses other than earning per share (EPS) can turn out to be high if the number of shares outstanding is reduced. Keywords: Profitability, Return on Equity (ROE), Earnings per Share (EPS), Stock Prices, Indonesia stock exchange (IDX)